2016
DOI: 10.1080/15287394.2015.1137264
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of niacin against methylmercury-induced genotoxicity and alterations in antioxidant status in rats

Abstract: This study investigates the potential beneficial effects of niacin (NA; vitamin B3) supplementation in rats chronically exposed to methylmercury (MeHg). Animals were randomly assigned to one of 4 groups (n = 6): Group I, control, received distilled water by gavage; Group II, received MeHg (100 µg/kg/d) by gavage; Group III, received NA (50 mg/kg/d) in drinking water; Group IV, received MeHg (100 µg/kg/d) by gavage + NA (50 mg/kg/d) in drinking water. Biochemical parameters levels of glucose, triglycerides, tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…These contradictory results are also inherent in animal studies. In rats Nath et al (1996) and more recently Silva de Paula et al (2016) noted no significant changes in CAT activity following exposure to Hg compounds, whereas Kong et al (2012) reported a decrease in activity levels during the embryonic development of a fish-model.…”
Section: New Perspectives: Mechanistic-based Biomarkersmentioning
confidence: 94%
See 3 more Smart Citations
“…These contradictory results are also inherent in animal studies. In rats Nath et al (1996) and more recently Silva de Paula et al (2016) noted no significant changes in CAT activity following exposure to Hg compounds, whereas Kong et al (2012) reported a decrease in activity levels during the embryonic development of a fish-model.…”
Section: New Perspectives: Mechanistic-based Biomarkersmentioning
confidence: 94%
“…Due to the electrophilic nature of Hg, once absorbed into the organism, it binds nucleophilic groups, such as thiols (SH) and selenols (SeH) in cysteine (Cys) and selenocysteine (Sec), respectively. Consequently, peptides and proteins containing these moieties are targeted by mercurials (Carvalho et al, 2008a; Farina et al 2009; Rooney 2007; Silva de Paula et al, 2016).…”
Section: Mercury Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the pathological role of the oxidative stress in development of diseases and new data on the antioxidant properties of nicotinic acid [12,14] and efficacy of complex compounds of germanium with nicotinic acid [2][3][4] the aim of this work is to study POM in cardiomyocytes and hepatocytes under the effect of nicotinic acid and the complex compound of germanium with nicotinic acid (MIGU-1) synthesized for the first time in the laboratory of the Department of General Chemistry and Polymers of the I.I.Mechnikov Odessa National University under the supervision of professor I.Y.Seifullina on the model of chronic intoxication with doxorubicin (CID) in rats.…”
mentioning
confidence: 99%